Financialisation as the core problem for a “Social Europe” - Andreas Nolke (Revista de Economía Mundial, 2017)
For more than three decades, increasing financialisation has been a core feature of the European economy. This process does not only lead to economic instability, but also to social inequality. A driving force of financialisation in Europe are the internal market institutions of the European Union, aggravated through the introduction of the Euro and the programmes for rescuing the common currency.